THE EFFECT OF BACK MASSAGE (EFFLEURAGE TECHNIQUE) ON CHANGES IN PAIN IN MOTHERS IN THE FIRST STAGE OF LABOR - Astutik, Puji; M.Wahyu Nur Arifin (Master of Public Health Program Universitas STRADA Indonesia, 2025)
Labor pain causes uncoordinated uterine activity resulting in prolonged labor, this can be overcome with back massage (effleurage technique) to help relaxation and reduce labor pain in the first stage. The purpose of this study was to determine the effect of back massage (effleurage technique) on changes in maternal pain in the first stage of labor in the delivery room of Nganjuk Regional Hospital. The design of this study was pre-experimental with a one group pre-posttest design approach. Conducted on October 3-7, 2023 in the delivery room of Nganjuk Regional Hospital. The population of this study was all mothers giving birth in the first stage, totaling 39 people. The sampling technique used Accidental Sampling with a sample of 20 respondents. The Independent Variable is back massage (effleurage technique), the Dependent Variable is changes in pain in mothers giving birth in the first stage. Data collection for the Independent Variable uses SOP and the Dependent Variable uses Observation. Statistical tests use Wilcoxon with α = 0.05. The results of the study showed that out of 20 respondents before being given back massage (effleurage technique), most had a moderate pain scale of 15 respondents (75%) and almost half had a severe pain scale of 5 respondents (25%). After being given massage, almost all had a moderate pain scale of 18 respondents (90%). Because respondents who had severe pain decreased to moderate pain of 5 respondents (25%) and those who had moderate pain decreased to mild pain of 2 respondents (10%). Based on the results of the Wilcoxon statistical test with α = 0.05 and obtained p (value) = 0.008 ≤ α (0.05) which means Ha is accepted and there is an effect of back massage (effleurage technique) on changes in pain in mothers in the first stage of labor in the delivery room of Nganjuk Regional Hospital. Back massage (effleurage technique) can reduce back pain, reduce muscle tension and increase blood circulation in areas that are painful in mothers in the first stage of labor. Thus, it can provide an analgesic or pain-relieving effect on mothers who are in labor.